Materiais híbridos orgânico-inorgânicos para o monitoramento e manejo sustentável de pragas de Coffea arabica L. - Soares, Walyson Silva (2022)
The combination of sodium alginate and nano-clay may result in the development of organic-inorganic hybrid materials with improved physicochemical properties. These materials may exhibit features such as sustained release of active compound and reduced environmental impact caused by reduced leaching and volatilization of the compounds. However, research related to the development of organic-inorganic hybrid materials for the monitoring and sustainable management of coffee tree pests has not yet been explored, especially for the management of the coffee berry borer Hypothenemus hampei Ferrari (Coleoptera: Curculionia), the rosette mealybug Planococcus citri Risso (Hemiptera: Pseudococcidae) and the leaf miner bug Leucoptera coffeella Guérin Mèneville (Lepidoptera: Lyonetidae). Thus, the objective of this study was to synthesize and characterize organic-inorganic hybrid materials for the monitoring and sustainable management of pests of the coffee tree, Coffea arabica L. In chapter 1, the hybrid material characterized biodegradable trap based on alginate-hectorite film with sustained release of attractant was synthesized and characterized at the Integrated Research Center of the Federal University of Viçosa, Campus Rio Paranaíba. The field experiments were conducted in three coffee fields, where traps were installed on the branches of the plants during two harvests. Thus, two treatments were considered (biodegradable and commercial traps), with three repetitions. Each plot was considered as a repetition. Evaluations were made every 15 days, with the objective of evaluating the population level, the effect of climatic conditions and phenological phases on the capture of the coffee berry borer. In chapter 2, the experiment was conducted in a randomized block experimental design with 4 repetitions, with the treatments composed of alginate-bentonite microsphere with and without thiamethoxam, thiamethoxam® 250 WG and control. The insecticides were applied to the soil at a depth of 1.0 cm under the projection of the crown of the coffee seedlings. Subsequently, evaluations were performed with the objective of verifying the toxicity of the alginate-bentonite microspheres with thiamethoxam to adult females of the rosette mealybug up to 21 days after application of the treatments. To evaluate the pupa and caterpillar of L. coffeella, the objective was to verify the toxicity and residual effect of thiamethoxam associated with the alginate-bentonite microspheres, at 28 and 44 days after treatment, respectively. The increase in the amount of dry fruits with galleries abandoned by the borer started at flowering, being the phase that marks the beginning of the emergence and flocking of colonizing females. The biodegradable trap showed 95.0% and 96.0% effectiveness in capturing the coffee berry borer compared to the commercial trap, in the 2019/2020 and 2020/2021 crop, respectively. Alginate-bentonite microspheres with thiamethoxam and thiamethoxam® 250 WG were not effective in controlling adult females of P. citri. However, 80% and 90% control of the pupa and caterpillar stages of the leaf miner bug was observed, respectively. It is concluded that organic-inorganic hybrid materials can be used for monitoring and sustainable management of coffee berry borer and leaf miner bug, and for rosette mealybug these materials were not effective.